Tumour-derived exosomal lncRNA-SOX2OT promotes bone metastasis of non-small cell lung cancer by targeting the miRNA-194-5p/RAC1 signalling axis in osteoclasts - Jianjiao Ni; Xiaofei Zhang; Juan Li; Zhiqin Zheng; Junhua Zhang; Weixin Zhao; Liang Liu (Cell Death and Disease, 2021)
Abstract Bone is a frequent metastatic site of non-small cell lung cancer (NSCLC), and bone metastasis (BoM) presents significant challenges for patient survival and quality of life. Osteolytic BoM is characterised by aberrant differentiation and malfunction of osteoclasts through modulation of the TGF-β/pTHrP/RANKL signalling pathway, but its upstream regulatory mechanism is unclear. In this study, we found that lncRNA-SOX2OT was highly accumulated in exosomes derived from the peripheral blood of NSCLC patients with BoM and that patients with higher expression of exosomal lncRNA-SOX2OT had significantly shorter overall survival. Additionally, exosomal lncRNA-SOX2OT derived from NSCLC cells promoted cell invasion and migration in vitro, as well as BoM in vivo. Mechanistically, we discovered that NSCLC cell-derived exosomal lncRNA-SOX2OT modulated osteoclast differentiation and stimulated BoM by targeting the miRNA-194-5p/RAC1 signalling axis and TGF-β/pTHrP/RANKL signalling pathway in osteoclasts. In conclusion, exosomal lncRNA-SOX2OT plays a crucial role in promoting BoM and may serve as a promising prognostic biomarker and treatment target in metastatic NSCLC.